2021
DOI: 10.35912/ijfam.v2i4.336
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate governance on financial performance of rural banks in Ghana

Abstract: Purpose: The study examined the influence of various corporate governance structures such as board size, board independence, board gender diversity and CEO duality on the financial performance of rural banks in Ghana. Research methodology: The study collected secondary data from the annual report of 30 rural banks for a 10-year period spanning 2010 to 2019. The data was coded into excel and exported into STATA where descriptive statistics, correlation analysis and regression analysis were adopted to answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…According to Hsu et al (2021), CEO duality was found to affect the firm performance of ROA negatively significantly. However, there were some inconsistent results where another study found that CEO duality does not affect a company's profitability (Musah & Adutwumwaa, 2021). Research by Law and Ningnan (2022) on Chinese firms found that CEO duality has a non-significant effect on the relationship with firm performance.…”
Section: Ceo Duality (Ceod)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hsu et al (2021), CEO duality was found to affect the firm performance of ROA negatively significantly. However, there were some inconsistent results where another study found that CEO duality does not affect a company's profitability (Musah & Adutwumwaa, 2021). Research by Law and Ningnan (2022) on Chinese firms found that CEO duality has a non-significant effect on the relationship with firm performance.…”
Section: Ceo Duality (Ceod)mentioning
confidence: 99%
“…However, Khan et al (2021) stated that CEO duality could be perceived as compromising the board's independence as one possesses a massive amount of power and authority. According to Musah and Adutwumwaa (2021), CEO duality will lead to biased decisions and cause one to monopolize. Imbalanced power will be created within the firm, resulting in ineffective and highly biased decisions.…”
Section: Ceo Duality (Ceod)mentioning
confidence: 99%
“…Responsible SMEs in developed countries have been widely studied by academics. However, given the differences between developing and developed countries in terms of sources of economic growth, institutional framework, and human development lags, it is not reasonable to extrapolate the findings and arguments of research undertaken in developed countries to developing ones (Bahta, Yun, Islam, & Bikanyi, 2021); (Musah & Adutwumwaa, 2021). SMEs are regarded as the backbone of developing economies, with an emphasis on entrepreneurship and job creation as important contributors to development and poverty reduction (Fox, 2004); (Singer, 2006); (Jamali, 2009).…”
Section: Csr and Innovation Similarities And Complementarity: Two Sid...mentioning
confidence: 99%
“…In this context, many studies emphasized the impact of governance structures on the financial performance of companies and their profitability (Musah & Adutwumwaa, 2021;Boachie, 2021). Meanwhile, some other studies have shown a relation between governance and the financial and operational performance of companies in various sectors (Aslam et al, 2021;Nasrallah & El Khoury, 2022).…”
Section: Third: the Strategy Of Governancementioning
confidence: 99%